2020
DOI: 10.1093/brain/awaa247
|View full text |Cite
|
Sign up to set email alerts
|

Variant-specific changes in persistent or resurgent sodium current in SCN8A-related epilepsy patient-derived neurons

Abstract: Missense variants in the SCN8A voltage-gated sodium channel gene are linked to early-infantile epileptic encephalopathy type 13, also known as SCN8A-related epilepsy. These patients exhibit a wide spectrum of intractable seizure types, severe developmental delay, movement disorders, and elevated risk of sudden unexpected death in epilepsy. The mechanisms by which SCN8A variants lead to epilepsy are poorly understood, although heterologous expression systems and mouse models have demonstrated altered sodium cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 62 publications
4
53
0
Order By: Relevance
“…Studies found that enhanced excitability of hiPSC-derived excitatory neurons is the primary mechanism underlying the gain-of-function Nav1.6 variant related seizure. 64 Loss-of-function variants of Nav1.6 are also found in patients, but these patients did not develop epileptic phenotypes. 65 In contrast, the association between variants in Nav1.2 and seizure are more complicated.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies found that enhanced excitability of hiPSC-derived excitatory neurons is the primary mechanism underlying the gain-of-function Nav1.6 variant related seizure. 64 Loss-of-function variants of Nav1.6 are also found in patients, but these patients did not develop epileptic phenotypes. 65 In contrast, the association between variants in Nav1.2 and seizure are more complicated.…”
Section: Discussionmentioning
confidence: 98%
“…Epilepsyassociated Nav1.6 variants are suggested to be gain-of-function. Study found that these gain-of-function Nav1.6 mutations led to enhanced excitability of excitatory neurons derived from hiPSCs, which are suggested as the main mechanism underlying the Nav1.6 variant related seizure (Tidball et al, 2020). Loss-of-function variants of Nav1.6 are also found in patients, but these patients do not have develop epileptic phenotypes (Gardella and Moller, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations